The Legal System of the Ship’s Agent Contract in the Iraqi and Comparative Law - Kareem Zghair, Assist. Prof. Dr. Aqeel (Basra studies journal, 2023)
Maritime transport is one of the most important means of commercial life since ancient times, as it is one of the oldest commercial businesses in transporting things and people, and today it is considered one of the most important means of transporting people and huge goods at all, for its ease and reasonable prices. The ship’s agent contract, or what is termed as the maritime agent contract, is the contract that regulates the relationship between the maritime agent on the one hand and the maritime carrier on the other hand and defines the rights and obligations of each of them. The most important of its obligations is the implementation of the maritime transport contract in the name and on behalf of the carrier and carrying out all the necessary legal work, whether in the contract of carriage of things or the contract of carriage of persons. Despite the importance of this contract in commercial life, it did not receive proper attention from the Iraqi legislator in terms of the laws regulating it compared to its great importance in commercial life. Therefore, in this article, we will discuss the ship’s agent contract guided by the Iraqi Maritime Agencies Law No. 56 of 1985 and related laws such as the Iraqi Transport Law No. 80 of 1983, and other comparative laws to clarify the general legal framework for this contract and the consequent rights and obligations of its parties.